1959
DOI: 10.1139/v59-255
|View full text |Cite
|
Sign up to set email alerts
|

Lycopodium Alkaloids: Viii. Lycopodine

Abstract: Information pertaining to the position of the carbonyl group relative t o the nitrogen atorn a n d to the size of one of the nitrogen rings in lycopodine has been obtained through n study of the reactions of a-arrcl 8-cyanobro~nolycopodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1960
1960
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The abromide I1 had been converted t o the corresponding acid and thence to the ring-A lacta~n IV. The infrared spectrum of the latter indicated that ring A was six-membered or larger (3). The p-bromide I11 had been converted to the corresponding acid which, on reduction with sodiunl borohydride, readily formed a lactone (V).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The abromide I1 had been converted t o the corresponding acid and thence to the ring-A lacta~n IV. The infrared spectrum of the latter indicated that ring A was six-membered or larger (3). The p-bromide I11 had been converted to the corresponding acid which, on reduction with sodiunl borohydride, readily formed a lactone (V).…”
mentioning
confidence: 99%
“…The methyl ester, IX, of P-cyanolycopodine carboxylic acid (3) was converted by hydrolysis and subsequent treatment with diazomethane t o the methyl ester of the corresponding anlino acid. When the ester was heated under reflux in xylene it yielded the lacta~n X , C1,jI-I2302N, which showed absorption in the infrared a t 1626 cm-l indicative of a six-membered or larger lactam.…”
mentioning
confidence: 99%